(untitled) (Research, Society and Development, 2021)
This systematic review aimed to evaluate the adherence to the CONSORT Statement in clinical studies comparing different instrumentation techniques in Endodontics. Methodology: A systematic search was carried out through Medline databases. There was no restriction on publication year or idiom. Solely randomized controlled trials (RCTs) were included. The articles were evaluated in compliance with CONSORT. Descriptive analyses of the number of studies by journal, country, and quality assessments were performed with RoB 2.0 Cochrane Collaboration’s tool for assessing risk of bias in RCTs. A total of 6779 studies were identified, and only 33 meet the eligibility criteria. In relation to the overall risk of bias, eight out of 33 were classified as at ‘low’ risk of bias. The overall CONSORT score for the included studies in this review was 22 ± 6.2 points. Significant differences among countries were observed (p = 0.03). The range of years had a significant influence on the average CONSORT score (p = 0.01). The adherence of RCTs of endodontic instrumentation to the CONSORT Statement requires improvements. Adherence to the CONSORT statement will also reduce the high or some concerns risk of bias of studies in the field. CRD42020160552